2006
DOI: 10.1158/1078-0432.ccr-05-1505
|View full text |Cite
|
Sign up to set email alerts
|

Expression of EphA2 and Ephrin A-1 in Carcinoma of the Urinary Bladder

Abstract: Purpose: The EphA2 receptor tyrosine kinase is believed to play a role in tumor growth and metastasis.The clinical significance of the expression of EphA2 was observed in breast, prostate, colon, skin, cervical, ovarian, and lung cancers. The purpose of this work was to determine the expression of EphA2 and its ligand, Ephrin A-1, and E-cadherin in carcinoma of the urinary bladder, and determine EphA2 as a new target for therapy in bladder cancer. Experimental Design: EphA2 mRNA and protein expression was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 33 publications
7
76
1
Order By: Relevance
“…EphA2 overexpression has been reported to correlate with aggressive features in other human tumor types [10][11][12][13][14][15][16][17][18][19]. Consistent with these reports, we found a significant increase in EphA2 expression in pancreatic cancers as compared to benign ducts and PanIN lesions, as well as increased expression in poorly differentiated carcinomas compared to well or moderate differentiated carcinomas (P < 0.005).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…EphA2 overexpression has been reported to correlate with aggressive features in other human tumor types [10][11][12][13][14][15][16][17][18][19]. Consistent with these reports, we found a significant increase in EphA2 expression in pancreatic cancers as compared to benign ducts and PanIN lesions, as well as increased expression in poorly differentiated carcinomas compared to well or moderate differentiated carcinomas (P < 0.005).…”
Section: Discussionsupporting
confidence: 90%
“…Instead, ephrinA binding seems to regulate EphA2 subcellular localization and interaction with other downstream signaling proteins including FAK and the MAP/ERK signaling pathways [8,9]. EphA2 is overexpressed in a variety of human cancers, and high levels of EphA2 are associated with aggressive disease and poor clinical outcomes [10][11][12][13][14][15][16][17][18][19]. In vitro studies have shown that EphA2 is a powerful oncoprotein, sufficient to confer malignant potential on non-transformed epithelial cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…This pattern was also reported on EphB4 expression in breast carcinomas, 31 EphA2 expression in bladder carcinomas, 32 and EphA7 expression in hepatocellular carcinomas. 18 The post-transcription regulation mechanisms interpreted EphB4 and EphA2 differential expression between protein and transcript.…”
Section: Downregulation Of Epha1 In Colorectal Carcinomassupporting
confidence: 80%
“…EFNA1 expression has been observed in tumor cells and in endothelial cells and has been shown to induce endothelial cell migration (18), capillary assembly in vitro and corneal angiogenesis in vivo (19). EFNA1 and EPHA2 expression is associated with carcinogenesis, angiogenesis (18,(20)(21)(22), and tumorigenesis in various types of cancer (23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%